Surveillance system using AVR ATMEGA16 - Yusfaizal, Mohamed Yusof (2009)
CCTV and other visual device had been use widely around us for various purposes, for traffic control, safety precaution and others. The image from the CCTV can serve as prove for crime or as reference in study. This project will aim to make the interface between CMOS camera C3088 with the AVR ATMEGA16 microcontroller. The communication for AVR and the computer is through serial port while the communication between AVR microcontroller to camera is using I²C protocol. HyperTerminal were used to send and receive serial data to and from computer. Microcontroller will process the command from the computer and based on these command, microcontroller will send appropriate data to the camera and ask the camera to capture and send photo back to the computer. The picture obtain from the camera can be use for surveillance or can be process for image processing purpose.